Evidence for allosteric effects on p53 oligomerization induced by phosphorylation. (8th December 2017) - Muller, Petr; Chan, Juliana M.; Simoncik, Oliver; Fojta, Miroslav; Lane, David P.; Hupp, Ted; Vojtesek, Borivoj
Abstract: p53 is a tetrameric protein with a thermodynamically unstable deoxyribonucleic acid (DNA)‐binding domain flanked by intrinsically disordered regulatory domains that control its activity. The unstable and disordered segments of p53 allow high flexibility as it interacts with binding partners and permits a rapid on/off switch to control its function. The p53 tetramer can exist in multiple conformational states, any of which can be stabilized by a particular modification. Here, we apply the allostery model to p53 to ask whether evidence can be found that the "activating" C‐terminal phosphorylation of p53 stabilizes a specific conformation of the protein in the absence of DNA. We take advantage of monoclonal antibodies for p53 that measure indirectly the following conformations: unfolded, folded, and tetrameric. A double antibody capture enzyme linked‐immunosorbent assay was used to observe evidence of conformational changes of human p53 upon phosphorylation by casein kinase 2 in vitro . It was demonstrated that oligomerization and stabilization of p53 wild‐type conformation results in differential exposure of conformational epitopes PAb1620, PAb240, and DO12 that indicates a reduction in the "unfolded" conformation and increases in the folded conformation coincide with increases in its oligomerization state. These data highlight that the oligomeric conformation of p53 can be stabilized by an activating enzyme and further highlight the utility of the allostery model when applied to understanding the regulation of unstable and intrinsically disordered proteins.